Penggunaan Model Pembelajaran Berbasis Masalah Terhadap Penigkatan Hasil Belajar Siswa Di Kelas XI SMK Negeri 2 Medan - Safnal Zeryo Sitepu; Saiful Bahri; Irham Habibi; Seprianti Harahap; Sartika Juwita Br Sinaga (Departement of Mathematics Education, 2024)
This research is conducted with the intention of enhancing the learning outcomes of students in class XI-TITL 4 at SMA Negeri 2 Medan through the implementation of a problem-based learning methodology. Two cycles of four stages—planning, doing, observing, and reflecting make up the classroom action research methodology. Thirty individuals, all from class XI-TITL 4, were the subjects of this study. Tests, observations, and documentation are the means of data gathering, while descriptive analysis is the tool of choice for data analysis. According to the study's findings, pupils' average mathematics learning outcomes also improved throughout the two cycles, rising from 70.83 to 79.48. Aside from that, cycle I had a completion rate of 57% and cycle II had a completion rate of 87% for student learning. The study that has been conducted suggests that instructional materials that employ a problem-based learning approach can enhance the learning outcomes for students.